Gender determination based on ct cranium measurements of adults in Hospital USM - Jamaluddin, Nurashikin (2015)

(untitled)
Purpose: The purpose of this study was to determine gender based on cranial measurements using Computed Tomography of adult. This study has not yet been done in this population. The measurements include the Glabello- Occipital Length (GOL), Basion- Nasion Length (BNL), Basion- Bregma length (BBL), Nasion- Bregma cord i.e. Frontal Chord (FRC), Bregma- Lambda i.e. Parietal Chord (PAC), Lambda- Opisthion i.e. Occipital Chord (OCC), Diploeic space 1 cm in front of the Bregma (DBB) and 1 cm behind lambda (DBL). Methods: A sample size of 180 adult patients in Hospital Universiti Sains Malaysia who underwent CT head were included in this study. The age taken was between the range of 18 years old and above. Images were reviewed in bone window. Results: The mean of glabello-occipital length, basion-nasion length, basion-bregma length, nasion - Bregma cord, Bregma- Lambda, Lambda- Opisthion and Diploeic space 1cm below lambda were statistically different between male and female. There was positive linear relationship for Glabello- Occipital Length, Basion- Bregma Length and Nasion Bregma cord between height and weight. Meanwhile Basion- Nasion Length only has a significant relationship with height. Conclusion: For this population, this study as well as other studies support for correlation in between certain cranial morphometry measurements with gender, height and weight. Thus, it might help to assist the future forensic radiology medicine using CT cranium to determine the gender, height and weight of patient or deceased.